1997
DOI: 10.2135/cropsci1997.0011183x003700010007x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Common Bean Performance under Drought Stress

Abstract: Drought is the second major constraint to common bean (Phaseolus vulga~s L) production after disease. This study examined yield under drought, yield potential, drought susceptibility index, harvest index, and geometric mean as potential indicators of drought resistant genotypes. The performance of two common bean populations, consisting of 78 and 95 recombinant inbred lines, was examined under moisture stress and nonstress regimes. Experiments were conducted at seven locations (1990-1994) in Michigan and Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
120
0
12

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(141 citation statements)
references
References 0 publications
9
120
0
12
Order By: Relevance
“…Rosales-Serna et al (2000) and Schneider et al (1997b) selected high-yielding drought-resistant lines when advanced recombinant inbred lines were evaluated across locations and years. Similarly, high-yielding drought-resistant lines were developed from double-cross interracial and inter-gene pool populations when F 5:7 lines were evaluated in replicated yield trials over years (Singh 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosales-Serna et al (2000) and Schneider et al (1997b) selected high-yielding drought-resistant lines when advanced recombinant inbred lines were evaluated across locations and years. Similarly, high-yielding drought-resistant lines were developed from double-cross interracial and inter-gene pool populations when F 5:7 lines were evaluated in replicated yield trials over years (Singh 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Among various morphological, physiological, phenological, yield, and yield-related traits to identify drought-resistant genotypes, mean seed yield (the arithmetic and geometric) of DS and NS environments was found to be the most effective selection criterion (White et al 1994a;Abebe et al 1998;Ramirez-Vallejo and Kelly 1998). Narrow-sense heritability for seed yield under drought stress ranged from 0.09 ± 0.19 to 0.80 ± 0.15 (White et al 1994b;Singh 1995;Schneider et al 1997b). Schneider et al (1997a) reported four random amplified polymorphic DNA (RAPD) markers in one bi-parental population, and five in another that were consistently associated with yield under DS, NS, and/or GM yield of DS and NS environments.…”
mentioning
confidence: 99%
“…La MG ha mostrado ser el criterio de selección más efectivo para resistencia a sequía en frijol; para su cálculo, se necesitan datos de rendimiento, riego y sequía, y es una medida del potencial rendimiento de cada genotipo (Abebe et al, 1998;Samper 1984). Para una selección efectiva de resistencia a sequía en frijol común, se ha propuesto basar la selección en una alta MG, seguida por selección para alto rendimiento bajo sequía (Schneider et al 1997).…”
Section: Introductionunclassified
“…Este arquetipo se mejoró en la línea de MSU con resistencia a sequía, B98311, derivada de la cruza entre la variedad "Raven" de la raza Mesoamericana (Kelly et al 1994) con la línea mejorada T-3016 con resistencia a sequía. T-3016 fue derivada de la cruza de Sierra/AC1028, y es una línea mejorada de la raza Durango de grano sin calidad comercial, identificada previamente como resistente a sequía en México y Michigan según la MG del rendimiento (Schneider et al 1997). La línea B98311 fue seleccionada por ser un genotipo de alto rendimiento bajo sequía severa en Michigan en 1998 (Kolkman y Kelly 1999).…”
Section: Introductionunclassified
“…Common bean (Phaseolus vulgaris L.) is produced mostly in regions of the world that typically experience a soil moisture deficit during the cropping season (Singh 1995;Schneider et al 1997). The reproductive phase of this crop is extremely vulnerable to soil moisture deficit (AcostaGallegos and Shibata 1989).…”
mentioning
confidence: 99%